Tzanakis score as a diagnostic tool for an acute appendicitis: An institution-based retrospective study - Shrestha, Devendra; Baral, Dilip (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Acute appendicitis is the most common pathology encountered among the patients with acute abdominal pain. Nowadays, different scoring systems are used to diagnose acute appendicitis. One of them is Tzanakis scoring, which is a combination of clinical examination, ultrasonography, and laboratory markers of inflammatory markers. Hence, this study was done to assess the diagnostic accuracy of Tzanakis scoring system in diagnosing acute appendicitis and compare its accuracy with histopathological examination.Methods: A retrospective observational study of all cases of acute appendicitis was conducted from July 2018 to June 2019 at the Department of Surgery, Western Regional Hospital.Out of 403 patients who had undergone appendicectomy during the period of one year, the necessary documents of 83 patients could not be collected. Hence, 320 patients were included in our study. The ethical approval was taken from the Institutional Review Committee (Ref. No. 14. 2077/078). Total Tzanakis score of all patients who underwent appendicectomy during this period was calculated and compared with histopathology report. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy were calculated.Results: The sensitivity,specificity of Tzanakis score of all 320 patients who underwent appendicectomy was 84% and 71% respectively. The diagnostic accuracy was 84% with positive predictive value 98% and negative predictive value 17%.Conclusions: The Tzanakis scoring system is simple, effective and easy to be applicable for the diagnosis of acute appendicitis.